Comparative genomic analysis provides insights into the genetic diversity and pathogenicity of the genus Brucella - Yang, Zilong; Chai, Zili; Wang, Xia; Zhang, Zehan; Zhang, Fengwei; Kang, Fuqiang; Liu, Wenting; Ren, Hongguang; Jin, Yuan; Yue, Junjie (Frontiers in Microbiology, 2024)
Some Brucella spp. are important pathogens. According to the latest prokaryotic taxonomy, the Brucella genus consists of facultative intracellular parasitic Brucella species and extracellular opportunistic or environmental Brucella species. Intracellular Brucella species include classical and nonclassical types, with different species generally exhibiting host preferences. Some classical intracellular Brucella species can cause zoonotic brucellosis, including B. melitensis, B. abortus, B. suis, and B. canis. Extracellular Brucella species comprise opportunistic or environmental species which belonged formerly to the genus Ochrobactrum and thus nowadays renamed as for example Brucella intermedia or Brucella anthropi, which are the most frequent opportunistic human pathogens within the recently expanded genus Brucella. The cause of the diverse phenotypic characteristics of different Brucella species is still unclear. To further investigate the genetic evolutionary characteristics of the Brucella genus and elucidate the relationship between its genomic composition and prediction of phenotypic traits, we collected the genomic data of Brucella from the NCBI Genome database and conducted a comparative genomics study. We found that classical and nonclassical intracellular Brucella species and extracellular Brucella species exhibited differences in phylogenetic relationships, horizontal gene transfer and distribution patterns of mobile genetic elements, virulence factor genes, and antibiotic resistance genes, showing the close relationship between the genetic variations and prediction of phenotypic traits of different Brucella species. Furthermore, we found significant differences in horizontal gene transfer and the distribution patterns of mobile genetic elements, virulence factor genes, and antibiotic resistance genes between the two chromosomes of Brucella, indicating that the two chromosomes had distinct dynamics and plasticity and played different roles in the survival and evolution of Brucella. These findings provide new directions for exploring the genetic evolutionary characteristics of the Brucella genus and could offer new clues to elucidate the factors influencing the phenotypic diversity of the Brucella genus.